2017
DOI: 10.1007/s10493-017-0191-1
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of Echinothrips americanus by phytoseiid predatory mites and the effect of pollen as supplemental food

Abstract: The poinsettia thrips, Echinothrips americanus Morgan, is an upcoming pest in greenhouse crops, causing serious damage in various vegetable and ornamental crops through extensive foliage feeding. We assessed which stages of E. americanus are attacked and killed by the phytoseiid predatory mites Amblyseius swirskii (Athias-Henriot), Amblydromalus limonicus (Garman and McGregor), Euseius gallicus Kreiter and Tixier and Euseius ovalis (Evans). Both the predation and oviposition rates were assessed in the laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 35 publications
0
14
0
6
Order By: Relevance
“…The suitability of a food source for a predator depends on both the nutritional content of the food and the nutritional requirement of the predator. An exclusive pollen diet is known to support the survival, development and reproduction of some phytoseiid species . It has already been demonstrated that N. californicus could survive, develop and oviposit successfully on a diet of almond pollen and maize pollen .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The suitability of a food source for a predator depends on both the nutritional content of the food and the nutritional requirement of the predator. An exclusive pollen diet is known to support the survival, development and reproduction of some phytoseiid species . It has already been demonstrated that N. californicus could survive, develop and oviposit successfully on a diet of almond pollen and maize pollen .…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary food resources can be nutritionally limiting for predators or they can support high rates of development and reproduction . Some supplementary foods may enable only predator survival while prey are unavailable .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the addition of Typha pollen had a positive effect on A. limonicus population on strawberries ( Fragaria x ananassa ) and cucumber ( C. sativus ) plants, and sharply reduced the density of western flower thrips ( F. occidentalis ) on cucumber ( C. sativus ) and greenhouse whitefly ( T. vaporariorum ) on bell peppers in greenhouses . Similarly, other studies demonstrated that combining A. swirskii and T. latifolia pollen significantly reduced whitefly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) and thrips Echinothrips americanus Morgan (Thysanoptera: Thripidae) under greenhouse trails . The addidition of alternative food on plant might decrease the strength of cannibalism .…”
Section: Discussionmentioning
confidence: 74%
“…37 Similarly, other studies demonstrated that combining A. swirskii and T. latifolia pollen significantly reduced whitefly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) and thrips Echinothrips americanus Morgan (Thysanoptera: Thripidae) under greenhouse trails. 63,70 The addidition of alternative food on plant might decrease the strength of cannibalism. 71 We therefore conclude that the combining application of supplemental food and phytoseiid mites to bell pepper could result in increased bio-control efficiency of TPP.…”
Section: Effect Of T Orientalis Pollenmentioning
confidence: 99%